Calibration and uncertainty of a head-discharge relationship for overshot gates under field conditions - Kutlu, Caner, author; Gates, Timothy K., advisor; Venayagamoorthy, Karan, committee member; Butters, Gregory, committee member (Colorado State University. Libraries, 2019)
Adjustable overshot gates (pivot weirs) are commonly used to control discharge and water levels in irrigation water delivery networks. The degree to which this control can be achieved depends upon reliable relationships between flow rate and the hydraulic head upstream and downstream of the gate. Moreover, such relationships also can be used for flow measurements. This study aims to develop a head-discharge equation for free flow over a overshot gate, to describe its uncertainty, and to examine the impact of gate submergence on the equation. Previous research on the flow characteristics of overshot gates has been performed primarily in laboratories, with very little investigation of performance in the field. This thesis provides a report of a field study conducted on four Obermeyer-type pneumatically automated overshot gates, which were operated for irrigation water delivery in northern Colorado. Utilizing both classical and amended forms of the sharp-crested weir equation, Buckingham-Pi dimensional analysis, and incomplete self-similarity theory, head-discharge equations for free flow have been developed which are alternately dependent on and independent of the gate inclination angle. To estimate the flow rate, three fully-suppressed Obermeyer-type overshot gates with crest widths of 22 ft, 20 ft, and 15 ft, and respective lengths of 5 ft., 6.3 ft., 6.08 ft , were inspected for eight different inclination angles (α = 22.8°, 23.6°, 29.7°, 32.6°, 34.6°, 35.3°, 38.9°, 40.4°), under free flow conditions. The best-performing equation is of classical form and contains a discharge coefficient dependent on gate inclination angle. It can be used to relate the discharge to upstream hydraulic head with about ± 10 % (standard deviation range of residual error) for free flow conditions. This equation is applicable for inclination angles between 20° and 40° and for flow rates ranging from 20 to 330 ft3/s. To reduce uncertainty of the discharge coefficient and to prevent the misleading consequences of neglecting the velocity head in the approaching flow, the total upstream energy head was employed in the equation. The effect of velocity head was significant for flow estimation. Dependency of the equation on the gate and field characteristics was examined by testing the equation with field data for a different type of overshot gate. Alternate equations were developed which altered the classical form for a sharp-crested weir to include both a coefficient and an exponent that are dependent upon gate inclination angle, and which preserved the classical form and treated the discharge coefficient as a constant independent of gate inclination. Although, satisfactory results were obtained for these alternative forms, inclusion of the angle in the discharge coefficient alone was recommended for higher accuracy of flow rate estimation, particularly for larger overshot gates with inclination angles ranging from about 20° to about 40°. Furthermore, the modular limit of the overshot gates was investigated for a fourth Obermeyer gate with a crest width of 17 ft and a length of 5.8 ft. Up to a submergence ratio of 0.51, the submergence effect was not observed to decrease the flow rate over for the gate. More data for a higher submergence conditions are required to develop a modular limit and a head-discharge equation for submerged flow.
Zip file contains ADCP readings data, field photos, and a field data table spreadsheet.